1967
DOI: 10.1126/science.158.3807.1459
|View full text |Cite
|
Sign up to set email alerts
|

Newts: Sun-Compass Orientation

Abstract: Rough-skinned newts, captured from breeding ponds, oriented on courses that would have intersected the familiar shorelines at right angles, when released in a circular arena on land under the sun or moon. Pondward migrants oriented similarly. Reorientation failed under complete cloud cover and after 7 days of darkness in an environmental chamber, but persisted in newts whose eyes were excised and in those displaced more than 27 kilometers in darkness. Both normal and blind animals compensated for displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The faithful return of adults to the same pond breeding season after breeding season is reminiscent of the homing behavior of the western red-bellied newt, Tarcih( ri'ularis, reported by Twitty (1959Twitty ( , 1961Twitty ( , 1966Twitty et al 1964) and Landreth and Ferguson (1967). Bennett (1970) demonstrated by experimental transplantation that adult red-spotted newts will return quickly to particular spots near shore when displaced to the middle or opposite end of a large lake.…”
Section: Contrary To the Reports Of Bennett (1970) Bishop (1941) Brmentioning
confidence: 91%
“…The faithful return of adults to the same pond breeding season after breeding season is reminiscent of the homing behavior of the western red-bellied newt, Tarcih( ri'ularis, reported by Twitty (1959Twitty ( , 1961Twitty ( , 1966Twitty et al 1964) and Landreth and Ferguson (1967). Bennett (1970) demonstrated by experimental transplantation that adult red-spotted newts will return quickly to particular spots near shore when displaced to the middle or opposite end of a large lake.…”
Section: Contrary To the Reports Of Bennett (1970) Bishop (1941) Brmentioning
confidence: 91%
“…Wiltschko et al (1978) reported that young homing pigeons seem to be dependent on route-based information. Landreth and Ferguson (1967) found an influence of the direction of the first leg in adult newts (Taricha granulosa) exposed to the sky during displacement. John Phillips has suggested to me that young alligators may need to rely on routebased guidance while they are learning the pattern of the gradients that allow multi-coordinate navigation.…”
Section: Route-based Navigationmentioning
confidence: 97%
“…Such orientation allows the animal to move in a given direction without the use of landmarks by using celestial cues in combination with a biological clock mechanism synchronized to local time to compensate for the rotation of the earth (34). Studies in frogs (78,79,81) and salamanders (80) showed that a laboratory-induced shift of the 24h lightdark cycle by 6h results in a 90°rotation in orientation. The orientational capabilities of these animals have been tested after various surgical manipulations and demonstrate that they can utilize either the eyes or extraocular photoreceptors located in the brain for compass orientation.…”
Section: Orientationmentioning
confidence: 98%
“…A more sophisticated type of orientation is the sun-compass orientation observed in many species of amphibians (78)(79)(80)(81). Such orientation allows the animal to move in a given direction without the use of landmarks by using celestial cues in combination with a biological clock mechanism synchronized to local time to compensate for the rotation of the earth (34).…”
Section: Orientationmentioning
confidence: 99%